FORMATION OF A SCHOOL OF MASTERS IN THE PERFORMANCE OF THE “G‘IJJAK” AND PERFORMANCE EXPERIENCES (World Bulletin of Education and Learning, 2026)
This article discusses the role and significance of the “G‘ijjak” instrument in the Uzbek performing status, the history of its development, as well as the features of the development of the Andijan school of “G‘ijjak”, and the practical experience of master musicians.
Keywords: Gijjak, music, performance, style, mastery, musicality, continuity, development, experience, mastery, performance.